Dealing With Immunoglobulin Shortages: A Rationalization Plan From Evidence-Based and Data Collection - Solís-Díez, Gerard; Turu-Pedrola, Marta; Roig-Izquierdo, Marta; Zara, Corinne; Vallano, Antoni; Pontes, Caridad (Frontiers in Public Health, 2022)
Background The demand and consumption of immunoglobulins (IgGs) are growing, and there are many difficulties in obtaining supplies. The aim of the study was to analyze the evolution of IgG consumption and cost over a decade, describe the measures implemented for clinical management in the context of regional public health system, and evaluate the initial impact of these measures. Methods We performed a retrospective longitudinal study including patients of all public health systems in Catalonia. First, we analyzed data on consumption and cost of IgGs during a period between 1 January, 2010 and 31 December 2021. Second, we analyzed the impact of a set of regional measures in terms of annual consumption and cost of IgGs. Regional measures were based on rational evidence-based measures and computer registries. We compared the data of year before applying intervention measures (1 January and 31 December 2020) with data of year after applying clinical management interventions (1 January and 31 December 2021). In addition, detailed information on clinical indications of IgG use between 1 January and 31 December 2021 was collected. Results Overall, in terms of population, the consumption of IgGs (g/1,000 inhabitants) increased from 40.4 in 2010 to 94.6 in 2021. The mean cost per patient increased from €10,930 in 2010 to €15,595 in 2021. After implementing the measures, the mean annual estimated consumption per patient in 2021 was statistically lower than the mean annual estimated consumption per patient in 2020 (mean difference −47 g, 95% CI −62.28 g, −31.72 g, p = 0.03). The mean annual estimated cost per patient in 2021 was also lower than the mean annual estimated cost per patient in 2020 (the mean difference was –€1,492, 95% CI –€2,132.12, –€851.88; p = 0.027). In 2021, according to evidence-based classification, 75.66% treatments were prescribed for a demonstrated therapeutic evidence-based indication, 12.17% for a developed therapeutic evidence-based indication, 4.66% for non-evidence-based therapeutic role indication, and 8.1% could not be classified because of lack of information. Conclusion The annual consumption and cost of IgGs have grown steadily over the last decade in our regional public health system. After implementing a set of regional measures, the annual consumption of IgGs per patient and annual cost per patient decreased. However, the decrease has occurred in the context of the coronavirus disease 2019 (COVID-19) pandemic, which may have influenced their clinical use. Managing the use of IgGs through a rational plan with strategies including evidence-based and data collection may be useful in a shortage situation with growing demand. Registries play a key role in collection of systematic data to analyze, synthesize, and obtain valuable information for decision support. The action developed needs close monitoring in order to verify its effectiveness.